Study design of the man and machine trial: a prospective international controlled noninferiority trial comparing manual with robotic catheter ablation for treatment of atrial fibrillation - Rillig, Andreas; Schmidt, Boris; Steven, Daniel; Meyerfeldt, Udo; Di Biase, Luigi; Wissner, Erik; Becker, Rüdiger; Thomas, Dierk; Wohlmuth, Peter; Gallinghouse, G. Joseph; Scholz, Eberhard P.; Jung, Werner; et al. (Journal of cardiovascular electrophysiology, 2013)
Study Design of the Man and Machine Trial. Background: Pulmonary vein isolation (PVI) has become the cornerstone procedure for the treatment of symptomatic drug-resistant atrial fibrillation (AF). At the present time, circumferential PVI (CPVI) using irrigated radiofrequency (RF) is the mostly used ablation technique. However, for CPVI, precise catheter navigation and excellent catheter stability is crucial thereby requiring experienced operators. Robotic navigation systems have been introduced to facilitate catheter navigation and to improve catheter stability, therefore potentially increasing procedural success and making CPVI accessible to less experienced operators. To date, no prospective randomized trial has evaluated the efficacy and safety of CPVI using RNS compared to manually performed ablation. Methods: In this prospective international multicenter noninferiority trial, 258 patients with either paroxysmal or short-standing persistent AF will be randomized for comparison of PVI using either manual or robotic ablation. In all patients, CPVI will be performed using irrigated RF ablation in combination with a 3D mapping system. The primary endpoint of the trial is the absence of AF or atrial tachycardia without antiarrhythmic drug therapy during 12-month follow-up. Secondary endpoints will be evaluation of periprocedural complications and procedural data such as procedure time, fluoroscopy time, as well as the incidence of esophageal injury assessed by endoscopy within 48 hours after the procedure. Conclusion: The “Man and Machine Trial” is the first prospective international randomized controlled multicenter noninferiority trial to compare manually performed CPVI with robotically navigated CPVI, evaluating both the safety and efficacy of the 2 techniques during a 12-month follow-up period. (J Cardiovasc Electrophysiol, Vol. 24, pp. 40-46, January 2013)
First published: 25 July 2012
Gesehen am 01.02.2022